Interchangeability of right ventricular longitudinal shortening fraction assessed by transthoracic and transoesophageal echocardiography in the perioperative setting: A prospective study - Beyls, Christophe; Huette, Pierre; Vangreveninge, Paul; Leviel, Florent; Daumin, Camille; Ammar, BenAmmar; Touati, Gilles; Roger, Bouzerar; Caus, Thierry; Dupont, Hervé; Abou-Arab, Osama; Momar, Diouf; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Conventional transthoracic (TTE) and transoesophageal echocardiography (TEE) parameters assessing right ventricle (RV) systolic function are daily used assuming their clinical interchangeability. RV longitudinal shortening fraction (RV-LSF) is a two-dimensional speckle tracking parameter used to assess RV systolic function. RV-LSF is based on tricuspid annular displacement analysis and could be measured with TTE or TEE. Objective The aim of the study was to determine if RV-LSFTTE and RV-LSFTEE measurements were interchangeable in the perioperative setting. Methods Prospective perioperative TTE and TEE echocardiography were performed under general anesthesia during scheduled cardiac surgery in 90 patients. RV-LSF was measured by semi-automatic software. Comparisons were performed using Pearson correlation and Bland-Altman plots. RV-LSF clinical agreement was determined as a range of −5 to 5%. Results Of the 114 patients who met the inclusion criteria, 90 were included. The mean preoperative RV-LSFTTE was 20.4 ± 4.3 and 21.1 ± 4.1% for RV-LSFTEE. The agreement between RV-LSF measurements was excellent, with a bias at −0.61 and limits of agreement of −4.18 to 2.97 %. All measurements fell within the determined clinical agreement interval in the Bland-Altman plot. Linear regression analysis showed a high correlation between RV-LSFTTE and RV-LSFTEE measurement (r = 0.9; confidence interval [CI] 95%: [0.87–0.94], p < 0.001). Conclusion RV-LSFTTE and RV-LSFTEE measurements are interchangeable, allowing RV-LSF to be a helpful parameter for assessing perioperative changes in RV systolic function. NCT NCT05404737. https://www.clinicaltrials.gov/ct2/show/NCT05404737.